Procedural units and fictive dialogue construction: the polyfunctionality of the German particle also. - Robles Sabater, Ferran (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This paper examines the use of the particle also in a corpus of fictive dialogues. It intends to establish which of its distinctive features are represented in these texts and in which ways they contribute to generate the illusion of authenticity that defines fictive orality. The data obtained show that also frequently takes very concrete positions within both the utterance and the turn, and expresses procedural meanings related to the structuring of dialogues, management of conversational topics, formulation of illocutionary acts or interpersonal metadiscourse, which diverge from those attributed to also by grammars. The research carried out confirms that also contributes to recreate the communicative conditions that are typical of spontaneous colloquial conversations and reproduces moves and functions inherent to them. The results obtained favour the analysis of also as a polysemic and polyfunctional particle.